(untitled) (London, 2004)
Therapists, trainee and established neurodevelopmental paediatricians and paediatric neurologists will all find this text an extremely useful and thorough grounding in this subject...very useful when talking to parents and older children about their difficulties and any proposed management plan
Keywords: Movement disorders in children,Cerebral palsy,Cerebral palsied children,Rối loạn vận động ở trẻ em,Bại não,Trẻ em bại não; Treatment,Treatment,Medical care,Điều trị,Điều trị,Chăm sóc y tế